Corporate venture capital and CSR performance: An extended resource based view's perspective - Battisti, Enrico; Nirino, Niccolò; Leonidou, Erasmia; Thrassou, Alkis (My University, 2022)
The purpose of this paper is to extend the Resource Based View (RBV) theory of companies, integrating it into a multidisciplinary context of analysis. Authors tested an empirical model in which corporate venture capital (CVC) impacts on corporate social responsibility (CSR) performance with the aim of creating a sustainable competitive advantage. The authors performed a longitudinal analysis, based on the Generalized Least Square (GLS) model, on 100 American and European companies reported in the Fortune Global 500 ranking from 2015 to 2019. The findings reveal that CVC programs have a positive impact on firm's environmental and social outcomes. They also broaden the boundaries of RBV theory analysis and contribute to corporate venture capital and corporate social responsibility literature. Additionally, authors develop insights applicable to practitioners to successfully implement CVC practices and CSR strategies jointly.
Keywords: Corporate social responsibility performance; Corporate venture capital; Resource based view; Corporate social responsibility strategy; ESG practices